Current-Mode Instrumentation Amplifiers - Safari, Leila; Ferri, Giuseppe; Minaei, Shahram; Stornelli, Vincenzo (Analog Circuits and Signal Processing, 2019)
This book describes a new way to design and utilize Instrumentation Amplifiers (IAs) by taking advantages of the current-mode (CM) approach. For the first time, all different topologies of CMIAs are discussed and compared, providing a single-source reference for instrumentation and measurement experts who want to choose a topology for a specific application. The authors also explain major challenges in designing CMIAs, so the book can be useful for anyone studying instrumentation amplifiers, and even other analog circuits. Coverage also includes various CM signal processing techniques employed in CMIAs, and applications of the CMIAs in biomedical and data acquisition are demonstrated. Discusses and compares all different current-mode instrumentation amplifier topologies; Includes a technical comparison, discussion, advantages and disadvantages of various current-mode instrumentation amplifiers, not available elsewhere; Explains in tutorial fashion major challenges caused by advancements in technology in instrumentation amplifier design.